2012
DOI: 10.1007/s13225-012-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

A multi-locus backbone tree for Pestalotiopsis, with a polyphasic characterization of 14 new species

Abstract: Pestalotiopsis is a taxonomically confused, pathogenic and chemically creative genus requiring a critical reexamination using a multi-gene phylogeny based on ex-type and ex-epitype cultures. In this study 40 isolates of Pestalotiopsis, comprised of 28 strains collected from living and dead plant material of various host plants from China were studied by means of morphology and analysis of ITS, β-tubulin and tef1 gene sequence data. Based on molecular and morphological data we describe 14 new species (Pestaloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(152 citation statements)
references
References 70 publications
(68 reference statements)
4
127
0
1
Order By: Relevance
“…These results reinforce those obtained by Maharachchikumbura et al (2012) who also found that tef1α had a higher discriminatory power in comparison to ITS and ß-tubulin. Combined sequence analysis of ITS, β-tubulin and tef1α genes successfully resolved all of the species used in this study with high bootstrap support.…”
Section: Multi-gene Phylogenysupporting
confidence: 91%
“…These results reinforce those obtained by Maharachchikumbura et al (2012) who also found that tef1α had a higher discriminatory power in comparison to ITS and ß-tubulin. Combined sequence analysis of ITS, β-tubulin and tef1α genes successfully resolved all of the species used in this study with high bootstrap support.…”
Section: Multi-gene Phylogenysupporting
confidence: 91%
“…Newly derived DNA sequences were deposited at GenBank (Benson et al 2010). The phylogenetic analyses were done using sequence data of select fungal species obtained from GenBank (Maharachchikumbura et al 2012. A maximum likelihood (ML) analyses was performed with a user-friendly, graphical, front-end software, raxmlGUI version 1.3 (Silvestro & Michalak 2012) using the settings of Maharachchikumbura et al (2013).…”
Section: Dna Pcr Amplification and Molecular Analysesmentioning
confidence: 99%
“…PCR was performed with the 25 μL reaction system consisting of 19.75 μL of double distilled water, 2.5 μL of 10× Taq buffer with MgCl 2 , 0.5 μL of dNTP (10 mM each), 0.5 μL of each primer (10 μM), 0.25 μL Taq DNA polymerase (5 U/μl), and 1.0 μL of DNA template. The thermal cycling program followed Maharachchikumbura et al (2012). The DNA sequences of ITS, beta-tubulin and tef1 regions generated in this study were submitted to GenBank.…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%
“…The Kishino-Hasegawa tests (Kishino & Hasegawa 1989) were performed in order to determine whether the trees inferred under different optimality criteria were significantly different. DNA sequences from our Pestalotiopsis isolates were com pared with those that originated from Maharachchikumbura et al (2012), with Seiridium sp. (SD096) as outgroup.…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%